COMPARATIVE EVALUATION BETWEEN INTRATHECAL HYPERBARIC ROPIVACAINE 0.75% ALONE VERSUS INTRATHECAL HYPERBARIC ROPIVACAINE 0.75% AND DEXMEDETOMIDINE IN LOWER ABDOMINAL SURGERIES - AAYUSHI; KAUR, PUNEETPAL; SHARMA, S. P. (International Journal of Current Pharmaceutical Research, 2025)
Objective: Spinal anesthesia is preferred for lower abdominal surgeries due to its benefits like reduced stress response and lower risk of complications. However, the limited duration of local anesthetics has led to the exploration of adjuvants like dexmedetomidine, which is known to enhance and prolong the anesthetic effect without significant respiratory depression. Methods: This prospective, randomized study involved 60 ASA I-II patients undergoing lower abdominal surgery, divided into three groups: Group A received intrathecal hyperbaric ropivacaine 0.75% with normal saline, Group B with ropivacaine 0.75% and 2.5 mcg dexmedetomidine, and Group C with ropivacaine 0.75% and 5 mcg dexmedetomidine. The study measured onset and duration of sensory and motor block, hemodynamic parameters, and side effects. Results: Adding dexmedetomidine enhanced the onset and duration of both sensory and motor blocks. Group C, which received 5 mcg dexmedetomidine, showed the fastest onset and longest duration of block, with stable hemodynamics and minimal side effects compared to ropivacaine alone. Conclusion: The study concludes that intrathecal dexmedetomidine at 5 mcg with ropivacaine 0.75% significantly improves the efficacy of spinal anesthesia for lower abdominal surgeries, suggesting that this combination could be an effective and safe option for enhancing surgical anesthesia.